Nausea and Vomiting Handling Behavior in terms of Parity and Level of Knowledge of First Trimester Pregnant Women in the Ngajum Health Center Work Area - Yulia Rahayuning; Sunarsih Sunarsih (PT. Griya Eka Sejahtera, 2022)
Background: Nausea and vomiting are normal and often found in pregnancy, especially in the first trimester of pregnancy. Prevention and treatment of nausea and vomiting carried out by pregnant women is strongly influenced by the knowledge possessed by pregnant women and parity. Nausea and vomiting in pregnant women who are not handled properly can cause dehydration to coma, while in the fetus it can occur LBW. Research Methods : This study used an observational analytic design with a cross sectional time approach . The population and sample in this study were all pregnant women who had experienced nausea and vomiting as many as 35 people in the Ngajum Health Center Work Area. The sample of this study were some pregnant women who had experienced nausea and vomiting, as many as 30 people were taken according to the researcher's criteria. Sampling using purposive sampling . Collecting data using a questionnaire and analyzed using the Spearman rank test . Research Results: This study showed that respondents with primigravida parity almost all had negative nausea and vomiting handling behavior, as many as 10 respondents (33.3%) . All respondents with poor knowledge have negative behavior in handling nausea and vomiting, as many as 4 respondents (40%). The results of this study indicate that there is a significant relationship between the behavior of handling nausea and vomiting in terms of knowledge and attitudes with a P value < 0.05 (0.000 < 0.05) . Conclusion: The behavior of pregnant women in the first trimester in handling nausea and vomiting is strongly influenced by the knowledge of pregnant women about nausea and vomiting and parity of pregnant women. it is hoped that health workers can provide midwifery care about nausea and vomiting in the first trimester of pregnancy, especially in primigravida and can increase efforts to overcome nausea and vomiting experienced by pregnant women in the first trimester. Meanwhile, pregnant women are expected to be more active in obtaining knowledge and care according to their needs. during pregnancy and frequent check-ups